The semiotic approach to the advertising image (methods and mechanisms) - sifoune, baya (Journal of Social Sciences and Humanities, 2021)
Due to the significant role of this image, this study aims to talk the importance of semiotics approach in the detection of mechanism and the ways in which they operate advertising spots in order to influence the gathering consciously and subconsciously. It also seeks disclosure of illusion and fantasy and imagination which always seeks about the advert speech to pass to the consumer relying on many rhetorical elements that are employed in pampering and guess. So what is the publicity? What are its main entrances theory? And how can you approach the advertising spots? And what are the most important rhetorical elements that can be employed by the image of advertising spots?